Endocrine therapy in the years following a diagnosis of breast cancer: A proof of concept study using the primary care prescription database linked to cancer registration data - Emanuel, G; Henson, K; Broggio, J; Charman, J; Horgan, K; Dodwell, D; Darby, S (Elsevier, 2019)
Introduction National cancer registration data were linked to the Primary Care Prescription Database (PCPD) in England. The level of endocrine therapy (ET) prescribed in women after a diagnosis of breast cancer was studied. Materials and Methods Cancer registrations for women diagnosed with breast cancer during 1995–2015, who survived to 31st March 2015, were linked to ET prescriptions issued during April–July 2015. Results Among 369 277 survivors of breast cancer diagnosed during 1995–2015, 37% were prescribed ET during April–July 2015. Among women whose breast cancer diagnosis was after 31st July 2010, 81% of those recorded with oestrogen receptor positive (ER+ve) disease were prescribed ET compared with only 6% of those with ER-ve disease. Younger women usually received tamoxifen and older women usually received aromatase inhibitors. Discussion The pattern of ET use observed in these data corresponds to that expected. This provides confidence in the potential of the PCPD for epidemiological research.